Electrospray Ionization Multiple Stage Quadrupole Ion-Trap and Tandem Quadrupole Mass Spectrometric Studies on Phosphatidylglycerol from Arabidopsis leaves - Hsu, Fong-Fu (2007)
Phosphatidylglycerol (PG) is the major phospholipid of plant chloroplasts. PG from Arabidopsis thaliana has an unusual fatty acyl chain, 3-trans-hexadecenoyl (Δ(3)16:1) in the sn-2 position of the major 18:3/Δ(3)16:1-PG species, as well as in 18:2/Δ(3)16:1-PG and 16:0/Δ(3)16:1-PG. Upon low-energy collisionally activated dissociation (CAD) in a tandem quadrupole or in an ion-trap mass spectrometer, the [M – H](−) ions of the PG molecules containing Δ(3)16:1 give product-ion spectra that are readily distinguishable from those arising from PGs without the Δ(3)16:1 species. The Δ(3)16:1-fatty acyl-containing PGs are characterized by MS(2) product-ion mass spectra that contain predominant [M – H – 236](−) ions arising from loss of the Δ(3)16:1-fatty acyl substituent as a ketene. This is attributable to the fact that the α-hydrogen of the Δ(3)16:1-fatty acid substituent involved in the ketene loss is an allylic hydrogen, which is very labile. This leads to preferential neutral loss of 236 and drastic decline in the neutral loss of 254 (i.e., loss as a fatty acid), the unique features that signify the presence of Δ(3)16:1-fatty acyl containing PGs. The neutral loss scan of 236, thus provides a sensitive tandem quadrupole mass spectrometric means to identify Δ(3)16:1-containing PG species in lipid mixtures. This low-energy tandem mass spectrometric approach also permits the structures of the Arabidopsis PGs that consist of two isomeric structures to be unveiled.